GO accelerate iron oxides formation and tetrabromobisphenol A removal enhancement in the GO loaded NZVI system. (1st January 2023) - Wang, Wenbing; Dong, Qianling; Mao, Yitao; Zhang, Yifan; Gong, Tiantian; Li, Hui
Abstract: Tetrabromobisphenol A (TBBPA) is an emerging persistent organic pollutant, which is very difficult to remove by common methods. In this study, the GO-load nanoscale zero-valent iron (NZVI/GO) was fabricated and optimized to improve the reaction rate and removal efficiency for TBBPA reliably and efficiently. The results showed that GO-load significantly reduced the self-aggregation of NZVI and the aggregate size decreased by 50.00% (1400–700 nm). Meanwhile, GO significantly improved the reaction rate k obs (1.11 ± 0.11 h −1 ) of TBBPA in the NZVI/GO system compared to the NZVI (0.40 ± 0.08 h −1 ) system, and this increment was more pronounced (177.5%) when the mass ratio of NZVI-to-GO reached 1.0 than other mass ratios. Furthermore, X-Ray Diffraction and X-ray photoelectron spectroscopy analysis suggested that the Fe 2+ transformation was changed and enriched by the GO. Only magnetite (Fe3 O4 ) was detected on the surface of NZVI, whereas the maghemite ( γ -Fe2 O3 ), hematite ( α -Fe2 O3 ), and Fe3 O4 were detected on the interface of NZVI/GO, which further performed the complexation adsorption through the –OH of TBBPA. This specific complexation adsorption is another potential accelerated removal mechanism for TBBPA and intermediates within the NZVI/GO system. This research has put forward a new perspective for widening the application of TBBPA removal using the synergistic effect between GO and NZVI. Graphical abstract: Image 1 Highlights: GO-load decreased the self-aggregation of NZVI and the aggregate size decreased by 50.00%. GO-load significantly improved the cycle life of NZVI/GO and reaction rate k obs of TBBPA. The increment of k obs was more pronounced (177.5%) when the ratio of ZVI to GO reached 1.0. GO-load enriched Fe 2+ transform pathways and induced γ -Fe2 O3, α -Fe2 O3, and Fe3 O4 generation.